The Model Minority and the Limits of Workplace Inclusion - Prasad, Ajnesh (Academy of Management Review, 2023)
In this article, I examine the model minority—a specific, understudied racialized other. To make sense of the position of the model minority in the contemporary workplace, I analyze the Netflix original series, The Chair. Juxtaposing The Chair against germane discourses related to the model minority, I consider some of the salient, though not fully understood, challenges to inclusion at work. I develop theoretical insights on how the model minority encounters specific forms of institutional racism that encumber their inclusion in organizations. Namely, I contend that the construction of an organizational member of color as the model minority effectively positions them in: (1) double consciousness, and, (2) the leadership conundrum. Double consciousness refers to the phenomenon wherein the model minority is subjected to latent or overt forms of institutional racism while, at the same time, pressured to remain within the restrictive parameters of the model minority stereotype. The leadership conundrum refers to how the model minority is cast with expectations to behave in ways not expected of their white colleagues who occupy the same role, which ultimately sets the model minority leader for failure. This article contributes to ongoing debates in critical diversity studies on the limits of workplace inclusion.